TRACE ELEMENT PARTITIONING BETWEEN PLAGIOCLASE AND MELT: INVESTIGATION OF DOPANT INFLUENCE ON PARTITION BEHAVIOR - Bindeman I.N.; Davis A.M. (My University, 2000)
We present results from an ion microprobe study of REE-doped and natural concentration plagioclase-basalt run products of Drake (1972) that carries on from our earlier study (Bindeman et al., 1998). The goals of this work are (1) to determine plagioclase/melt partition coefficients for all REE for four analyzed plagioclase compositions (An40–80); and (2) to determine whether doping with REE influences partition coefficients of other REE and other trace elements. In combination with our analyses of Sr-doped runs (Bindeman et al., 1998), the new data allow us to compare partition coefficients (Dι’s) of trace elements at natural concentrations with those in REE-doped and Sr-doped runs. In these comparisons, runs have the same run temperature and compositions, but different doping element(s).